All-fiber thulium/holmium-doped mode-locked laser by tungsten disulfide saturable absorber. (25th November 2016) - Yu, Hao; Zheng, Xin; Yin, Ke; Cheng, Xiang'ai; Jiang, Tian
Abstract: A passively mode-locked thulium/holmium-doped fiber laser (THDFL) based on tungsten disulfide (WS2 ) saturable absorber (SA) was demonstrated. The WS2 nanosheets were prepared by liquid phase exfoliation method and the SA was fabricated by depositing the few-layer WS2 nanosheets on the surface of a fiber taper. The modulation depth, saturable intensity, and non-saturable loss of this SA were measured to be 8.2%, 0.82 GW cm −2, and 29.4%, respectively. Based on this SA, a stable mode-locked laser operated at 1.91 µ m was achieved with pulse duration of 825 fs and repetition rate of 15.49 MHz, and signal-to-noise ratio (SNR) of 67 dB. Meanwhile, by increasing the pump power and adjusting the position of polarization controller, harmonic mode-locking operations were obtained. These results showed that the WS2 nanosheet-based SA could be served as a desirable candidate for a short-pulse mode locker at 2 µ m wavelength.